Ebola Virus Infection Induces HCAR2 Expression Leading to Cell Death - Makoto, Kuroda; Peter J, Halfmann; Yoshihiro, Kawaoka (The Journal of Infectious Diseases, 2023)
Abstract Ebola virus (EBOV) induces cell death not only in infected permissive cells but also in nonpermissive, bystander cells by employing different mechanisms. Hydroxycarboxylic acid receptor 2 (HCAR2) has been reported to be involved in apoptotic cell death. We previously reported an increase in the expression of HCAR2-specific mRNA in EBOV-infected individuals with fatal outcomes. Here, we report that infection with an EBOV lacking the VP30 gene (EBOVΔVP30) results in the upregulation of HCAR2 mRNA expression in human hepatocyte Huh7.0 cells stably expressing VP30. Transient overexpression of HCAR2 reduced the viability of Huh7.0 cells and human embryonic kidney cells. Phosphatidylserine externalization and cell membrane permeabilization by HCAR2 overexpression was also observed. Interestingly, coexpression of HCAR2 with EBOV VP40 further reduced cell viability in transfected cells compared to HCAR2 coexpression with other viral proteins. Our data suggest that HCAR2 may contribute to EBOV-induced cell death.